SCHILLER'S DRAMA SCHILLER'S DRAMA - Ходжаева Нафиса Ахмаджоновна; Фозилова Фарангиз Отабековна (Journals Park Publishing, 2026)
This article examines the characteristics of Friedrich Schiller's drama, his artistic method, philosophical ideas, and contribution to world literature. Particular attention is given to the analysis of the playwright's major works, their themes, artistic features, and ideological content.
Keywords: Drama, Schiller, German literature, Romanticism, Classicism, theater, artistic method, personal freedom.